2021
DOI: 10.1186/s12879-021-06112-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of enterovirus genotypes in the cerebrospinal fluid of children associated with aseptic meningitis in Liaocheng, China, from 2018 to 2019

Abstract: Background Aseptic meningitis is most often caused by enteroviruses (EVs), but EVs associated with aseptic meningitis have not yet been reported in Liaocheng. The aim of this study was to determine the prevalence and genetic characteristics of EVs causing aseptic meningitis in children in Liaocheng. Methods We reviewed the epidemiological and clinical characteristics of 504 paediatric cases of aseptic meningitis in Liaocheng from 2018 to 2019 and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…Within the EVSurv, mainly stool samples or CSF from patients with polio-compatible symptoms, i.e., suspected aseptic meningitis/encephalitis or AFP, are tested for the presence of enteroviruses. Since 2006, approximately 25% of the samples have been enterovirus positive each year, which is in line with data from other countries [69][70][71][72][73], although data vary due to differences in study design, case definitions, sample type and age groups considered [71,74,75]. In recent years annual sample numbers and overall positivity rate have slightly decreased in Germany.…”
Section: Discussionsupporting
confidence: 76%
“…Within the EVSurv, mainly stool samples or CSF from patients with polio-compatible symptoms, i.e., suspected aseptic meningitis/encephalitis or AFP, are tested for the presence of enteroviruses. Since 2006, approximately 25% of the samples have been enterovirus positive each year, which is in line with data from other countries [69][70][71][72][73], although data vary due to differences in study design, case definitions, sample type and age groups considered [71,74,75]. In recent years annual sample numbers and overall positivity rate have slightly decreased in Germany.…”
Section: Discussionsupporting
confidence: 76%
“…Unfortunately, in this study, the number of days between symptom onset and sampling was not available. In line with previous studies [ 9 , 12 ], our findings showed that the incidence of aseptic meningitis by EV in males is higher than in females, although the difference is not statistically significant. As shown in previous studies, most cases of aseptic meningitis were observed in summer and autumn.…”
Section: Discussionsupporting
confidence: 92%
“…The differences in prevalence between the different studies could be attributed to the test method and population of patients, and factors such as age group, sampling time, sample storage and transport, season, sporadic cases or an outbreak, and the high variability of the viral genes or other viral infections. [ 17 , 18 ] In this study, the most frequent cause of viral meningitis was EVs infection, followed by VZV and HSV infection. In America, in addition to EVs and various arboviruses, HSV and VZV have also been frequently isolated in patients with aseptic meningitis.…”
Section: Discussionmentioning
confidence: 78%